CONCEPT OF PROTECTION AGAINST COMPUTER VIRUSES AND DETECTION PERFORMANCE Trojan trojan virus - Maria Sri Wulandari (Majalah SIKOMTEK, 2005)
Computer security is not considered important by many people apparently can take a big lossfor that person. If further research proved many things - things that can threaten data -personal data through computer media. There is now a lot of programs - programs that aremalicious as viruses, worms, trojans and other when infecting our computer system mayresult in losses for us. Trojan Horse or better known as the "Trojan" in the computer system ispart of a digital infection whose presence is not expected by the owner of the computer.Trojan consisting of the functions of unknown purpose, but in broad outline has destructiveproperties.Trojans go into a computer over a network is inserted at the time by surfing with physicalmedia. Trojan does not take effect directly as well as computer viruses, but the potentialhazards can be far greater than computer viruses. Trojans can be activated and controlledremotely or by timer. Remote control as the Remote Administration Tools, which is theserver version will be controlled by the attacker through his version of the client. Many thingscan be done by an attacker if the victim's computer that has been controlled. Certain unusualports open trojan indicate active events.Handling Trojan can be done in two ways, n